Interpretation of the Phenomenon of Nihilism in Research by Western Scholars - Safarova, Markhabo (International Journal on Integrated Education, 2023)
Nihilism is a philosophical concept that has been debated for centuries, and its interpretation has evolved over time. In this scientific article, we explore the phenomenon of nihilism and its interpretation by Western scholars. We examine the historical context of nihilism and the various interpretations of the concept by Western scholars. We also discuss the impact of nihilism on contemporary society and the implications for future research. Our analysis reveals that nihilism has been interpreted in different ways by Western scholars, ranging from a rejection of traditional values and beliefs to a more radical rejection of all meaning and purpose in life. We find that nihilism has had a significant impact on contemporary society, particularly in the areas of politics, culture, and religion. The article provides a comprehensive analysis of the phenomenon of nihilism and its interpretation by Western scholars. We argue that a deeper understanding of nihilism is necessary to address its impact on contemporary society and to inform future research in this area. Our article contributes to the ongoing debate on nihilism and provides a valuable resource for scholars interested in this topic.